O papel da liderança nos microfundamentos da capacidade absortiva e no desempenho organizacional em organizações educacionais - Martins, Lisiane de Cássia Tier (2021)
This research seeks to highlight the existing knowledge related to the microfoundations of Absorptive Capacity, specifically the importance of Leadership for the development and impact it has on organizational performance, delimiting the analysis and systematization from the perspective of research with a sample of intermediate leaders who work in educational organizations. Using the quantitative method, confirmatory factor analysis was adopted to validate measures and structural equations, aiming to test hypotheses raised to support the proposed theoretical model. As a result, it was found that ACAP impacts the organizational performance of professional educational services, expanding the generation of new knowledge, as well as existing knowledge, to achieve results and generate value for the business. The contributions evidenced a better understanding of the absorption of knowledge by leaders through the acquisition, assimilation, transformation and application of this knowledge in achieving organizational performance, as well as factors that can infer the development of managerial capabilities. Among the possibilities for future research, we suggest exploring other instruments for analyzing the themes investigated, the possibility of qualitative analysis of the hypotheses not supported in the study, verification of the impact of ACAP, organizational performance and different leadership styles with other means of investigation and the exploration of the problem researched in other organizational realities.